Child-Centered Learning In The Home Environment: Implementation And Challenges - Gondiawati, Nani; Nurhayati, Sri (Universitas Nusantara PGRI Kediri, 2024)
This study examined the implementation of child-centered learning principles by the parents of TK Al Muthmainnah students, their knowledge of these principles, and the challenges they faced. A qualitative case study method was adopted, with ten parents participating as primary informants. Data were collected through observations, in-depth interviews, and document analysis, and were analyzed using a thematic analysis approach. The analysis revealed that parents possessed a foundational understanding of child-centered learning, viewing it as a way to foster autonomy and cater to their children's interests. They applied these principles at home by allowing children to make choices and encouraging exploration. However, they encountered challenges such as limited resources and the need for balancing guidance with children's independence. The findings suggest that while parents are inclined towards child-centered practices, the efficacy of these practices is affected by the availability of resources and support